SMMEs’ business mindset on tax compliance in North West: Perceptions and challenges - Janine Myburg; Daniel Schutte (The Southern African Journal of Entrepreneurship and Small Business Management, 2025)
Background: The economic development of South Africa heavily relies on small, medium and micro-enterprises (SMMEs), which face significant difficulties in meeting tax obligations because of their perceived complexity of regulations and a decline in trust towards government institutions.